Recommendations for the use of Serious Games in people with Alzheimer's Disease, related disorders and frailty - Robert, Philippe; König, Alexandra; Amieva, Hélene; Andrieu, Sandrine; Bremond, François; Bullock, Roger; Ceccaldi, Mathieu; Dubois, Bruno; Gauthier, Serge; Kenigsberg, Paul-Ariel; Nave, Stéphane; Orgogozo, Jean Marc; et al. (Frontiers in Aging Neuroscience, 2014)
Alzheimer’s disease and other related disorders (ADRD) represent a major challenge for health care systems within the aging population. It is therefore important to develop better instruments to assess the disease severity and progression, as well as to improve its treatment, stimulation, and rehabilitation. This is the underlying idea for the development of Serious Games (SG). These are digital applications specially adapted for purposes other than entertaining; such as rehabilitation, training and education. Recently, there has been an increase of interest in the use of SG targeting patients with ADRD. However, this field is completely uncharted, and the clinical, ethical, economic and research impact of the employment of SG in these target populations has never been systematically addressed. The aim of this paper is to systematically analyse the Strengths, Weaknesses, Opportunities and Threats (SWOT) of employing SG with patients with ADRD in order to provide practical recommendations for the development and use of SG in these populations. These analyses and recommendations were gathered, commented on and validated during a 2-round workshop in the context of the 2013 Clinical Trial of Alzheimer’s Disease (CTAD) conference, and endorsed by stakeholders in the field. The results revealed that SG may offer very useful tools for professionals involved in the care of patients suffering from ADRD. However, more interdisciplinary work should be done in order to create SG specifically targeting these populations. Furthermore, in order to acquire more academic and professional credibility and acceptance, it will be necessary to invest more in research targeting efficacy and feasibility. Finally, the emerging ethical challenges should be considered a priority.